Distinct Contributions of Dorsal and Ventral Streams to Imitation of Tool-Use and Communicative Gestures. (1st December 2016) - Dressing, Andrea; Nitschke, Kai; Kümmerer, Dorothee; Bormann, Tobias; Beume, Lena; Schmidt, Charlotte S M; Ludwig, Vera M; Mader, Irina; Willmes, Klaus; Rijntjes, Michel; Kaller, Christoph P; Weiller, Cornelius; et al.
Abstract: Imitation of tool-use gestures (transitive; e.g., hammering) and communicative emblems (intransitive; e.g., waving goodbye) is frequently impaired after left-hemispheric lesions. We aimed 1) to identify lesions related to deficient transitive or intransitive gestures, 2) to delineate regions associated with distinct error types (e.g., hand configuration, kinematics), and 3) to compare imitation to previous data on pantomimed and actual tool use. Of note, 156 patients (64.3 ± 14.6 years; 56 female) with first-ever left-hemispheric ischemic stroke were prospectively examined 4.8 ± 2.0 days after symptom onset. Lesions were delineated on magnetic resonance imaging scans for voxel-based lesion-symptom mapping. First, while inferior-parietal lesions affected both gesture types, specific associations emerged between intransitive gesture deficits and anterior temporal damage and between transitive gesture deficits and premotor and occipito-parietal lesions. Second, impaired hand configurations were related to anterior intraparietal damage, hand/wrist-orientation errors to premotor lesions, and kinematic errors to inferior-parietal/occipito-temporal lesions. Third, premotor lesions impacted more on transitive imitation compared with actual tool use, pantomimed and actual tool use were more susceptible to lesioned insular cortex and subjacent white matter. In summary, transitive and intransitive gestures differentially rely on ventro-dorsal and ventral streams due to higher demands on temporo-spatial processing (transitive) or stronger reliance on semantic information (intransitive), respectively.